Polyhydroxybutyrate (PHB) Production Using an Arabinose-Inducible Expression System in Comparison With Cold Shock Inducible Expression System in Escherichia coli - Napathorn, Suchada Chanprateep; Visetkoop, Sirirat; Pinyakong, Onruthai; Okano, Kenji; Honda, Kohsuke (Frontiers in Bioengineering and Biotechnology, 2021)
Cupriavidus necator strain A-04 has shown 16S rRNA gene identity to the well-known industrial strain C. necator H16. Nevertheless, the cell characteristics and polyhydroxyalkanoate (PHA) production ability of C. necator strain A-04 were different from those of C. necator H16. This study aimed to express PHA biosynthesis genes of C. necator strain A-04 in Escherichia coli via an arabinose-inducible expression system. In this study, the PHA biosynthesis operon of C. necator strain A-04, consisting of three genes encoding acetyl-CoA acetyltransferase (phaAA–04, 1182 bp, 40.6 kDa), acetoacetyl-CoA reductase (phaBA–04, 741 bp, 26.4 kDa) and PHB synthase Class I (phaCA–04, 1770 bp), was identified. Sequence analysis of the phaAA–04, phaBA–04, and phaCA–04 genes revealed that phaCA–04 was 99% similar to phaCH16 from C. necator H16. The difference in amino acid residue situated at position 122 of phaCA–04 was proline, whereas that of C. necator H16 was leucine. The intact phaCABA–04 operon was cloned into the arabinose-inducible araBAD promoter and transformed into E. coli strains Top 10, JM109 and XL-1 blue. The results showed that optimal conditions obtained from shaken flask experiments yielded 6.1 ± 1.1 g/L cell dry mass (CDM), a PHB content of 93.3 ± 0.9% (w/w) and a productivity of 0.24 g/(L⋅h), whereas the wild-type C. necator strain A-04 accumulated 78% (w/w) PHB with a productivity of 0.09 g/(L⋅h). Finally, for the scaled-up studies, fed-batch cultivations by pH-stat control in a 5-L fermenter of E. coli strains XL1-Blue harboring pBAD/Thio-TOPO-phaCABA–04 and pColdTF-phaCABA–04 in MR or LB medium, leading to a PHB production of 31.4 ± 0.9 g/L at 54 h with a PHB content of 83.0 ± 3.8% (w/w), a CDM of 37.8 ± 1.2 g/L, a YP/S value of 0.39 g PHB/g glucose and a productivity of 0.6 g PHB/(L⋅h) using pColdTF-phaCABA–04 in MR medium. In addition, PHB production was 29.0 ± 1.1 g/L with 60.2 ± 2.3% PHB content in the CDM of 53.1 ± 1.0 g/L, a YP/S value of 0.21 g PHB/g glucose and a productivity of 0.4 g PHB/(L⋅h) using pBAD/Thio-TOPO-phaCABA–04 in LB medium. Thus, a relatively high PHB concentration and productivity were achieved, which demonstrated the possibility of industrial production of PHB.